INFLUENCE OF BOTANICALS ON SOIL FERTILITY POTENTIALS, SEED GERMINATION AND PERFORMANCE OF MAIZE (ZEA MAYS) VARIETIES UNDER LOW FERTILE CONTINUOUSLY-CROPPED SOIL CONDITIONS - Peter, Babajide; OpasinaIfeoluwa; Adijat, Ajibola; Noah; Temitope, Oyedele; Oyatokun (International Journal of Research -GRANTHAALAYAH, 2017)
It is not unreasonable to state that, even before the introduction of organic agriculture, African local farmers have numerous of undocumented environment-friendly, nature-inclined indigenous techniques for boosting soil fertility and enhancing crop yield. However, despite the versatility of indigenous knowledge, setback is always experienced from western science, which tags such knowledge as being non-scientific and not worthy of scholarly engagements. A field experiment was carried out in the year 2013, at the Teaching and Research Farms, LadokeAkintola University of Technology, Ogbomoso, to assess the soil fertility and yield promoting potentials of some indigenous plant species’ botanicals used as pre-planting treatments on different maize varieties. It was a 3 by 5 factorial experiment. The treatments introduced were: Three (3) maize varieties (V1 = ACR-DMR-SR-Y, V2 = Local EM-W and V3 = Suwan Solo Yellow and five (5) other treatments (comprising pre-sowing botanical treatments of: Kigeliaafricana only, Glyphea brevis only, combination of Kigeliaafricana and Glyphea brevis only, NPK fertilizer application (as a reference) and the control (treated with ordinary water only). The trial was laid out in Split Plot in Randomized Complete Block Design (RCBD), replicated three times. Data were collected on growth and yield parameters, and the data collected were analysed using analysis of variance (ANOVA). Means were compared using Duncan Multiple Range Test (DMRT). All the botanical treatments significantly influenced germination, growth, yield and nutrient uptakes of maize, compared to the control. Either of the botanicals tested (with ordinary basal manure application of the pre-existing plant residues on the field), competed effectively with NPK fertilized plants. Hence, since maize responded better to sole treatments of either Kigeliaafricana or Glyphea brevis extracts, irrespective of varieties than the combined treatment of the two botanicals, any of the maize varieties is therefore recommended as being suitably compatible with either of the sole botanical treatments, in the study area. Thus, this research is reasonable, particularly in the aspects of fertilizer economy, environment-friendliness, organic farming and more profitable crop production in the tropics, where soils are continuously cropped and marginal.